2009
DOI: 10.1186/1471-2105-10-s1-s65
|View full text |Cite
|
Sign up to set email alerts
|

A random forest approach to the detection of epistatic interactions in case-control studies

Abstract: Background: The key roles of epistatic interactions between multiple genetic variants in the pathogenesis of complex diseases notwithstanding, the detection of such interactions remains a great challenge in genome-wide association studies. Although some existing multi-locus approaches have shown their successes in small-scale case-control data, the "combination explosion" course prohibits their applications to genome-wide analysis. It is therefore indispensable to develop new methods that are able to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
216
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(220 citation statements)
references
References 36 publications
2
216
0
2
Order By: Relevance
“…Interacting predictors that both have no A simple graphical method which might help to identify predictors involved in interactions consists in plotting the RF VIMs (which may also capture interaction effects) against a standard univariate statistic, see e.g. [40,50]. In the first step, a subset of potentially interesting predictors is extracted using RF.…”
Section: Predictors Involved In Interactionsmentioning
confidence: 99%
“…Interacting predictors that both have no A simple graphical method which might help to identify predictors involved in interactions consists in plotting the RF VIMs (which may also capture interaction effects) against a standard univariate statistic, see e.g. [40,50]. In the first step, a subset of potentially interesting predictors is extracted using RF.…”
Section: Predictors Involved In Interactionsmentioning
confidence: 99%
“…Bureau et al [2005] created a modification of pVI to look at the joint effects for pairs of SNPs. Jiang et al [2009] proposed a sliding window VI measure for examining interactions.…”
Section: Other Variable Importance Measuresmentioning
confidence: 99%
“…While there is potentially room for the development of VI measures that explicitly examine interactions, little work has been performed to this point. In one of the few known methods, Jiang et al [2009] proposed a sliding window method to scan for up to three-way interactions.…”
Section: Interaction Detectionmentioning
confidence: 99%
“…However, direct application of RF to GWAS still poses a real challenge, and only a few studies were reported in the literature. 14,17,[19][20][21] The difficulty lies in the poor quality of estimates of variables' importance when huge forests are constructed indiscriminately from the whole data, where the majority of the variables are noise. This obstacle must be overcome for GWAS applications of RF to be practically useful.…”
Section: Introductionmentioning
confidence: 99%